2010
DOI: 10.3390/molecules15010432
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Effects of Three Different Mitragyna speciosa Korth Leaf Extracts on Phase II Drug Metabolizing Enzymes—Glutathione Transferases (GSTs)

Abstract: In the present study, we investigate the effects of three different Mitragyna speciosa extracts, namely methanolic, aqueous and total alkaloid extracts, on glutathione transferase-specific activity in male Sprague Dawley rat liver cytosol in vitro and in vivo. In the in vitro study, the effect of Mitragyna speciosa extracts (0.01 to 750 µg/mL) against the specific activity of glutathione transferases was examined in rat liver cytosolic fraction from untreated rats. Our data show concentration dependent inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…The effect of recently published substances in M. speciosa (alkaloids, flavonoids, saponins, triterpenoid saponins, and glycoside derivatives) [29] on health and, in particular, on the liver are not studied well. A recent study showed a slight elevation in glutathione-S-transferase in mice after administration of M. speciosa extracts [30] as a possible sign of strain on the liver. Other than that, toxicity studies are rare and do not show relevant toxicity in most reports.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of recently published substances in M. speciosa (alkaloids, flavonoids, saponins, triterpenoid saponins, and glycoside derivatives) [29] on health and, in particular, on the liver are not studied well. A recent study showed a slight elevation in glutathione-S-transferase in mice after administration of M. speciosa extracts [30] as a possible sign of strain on the liver. Other than that, toxicity studies are rare and do not show relevant toxicity in most reports.…”
Section: Discussionmentioning
confidence: 99%
“…4.44 μg /ml or equally to 4.4% w/w of mitragynine was quantified in MMS which was consistent with earlier published reports (Jansen and Prast, 1988a; Ponglux et al, 1994; Chittrakarn et al, 2010). Mitragynine, being the maximum dominant active alkaloid present in M. speciosa is responsible for the diverse pharmacological activities of this plant (Azizi et al, 2010). Interestingly, mitragynine significantly inhibited the dopamine (D 2 ) and serotonin (5-HT 2 ) receptors in a radioligand-binding assay (Boyer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since they share a typical chemical skeleton with different structural conformation or substitution patterns. On the other hand, toxicity is a truly complex phenomenon that is in uenced by several factors like cellular penetration, diffusion, distribution, metabolism, innate toxicity of the agent, and target cell speci cations [23][24].…”
Section: Discussionmentioning
confidence: 99%